Праздник непослушания: повесть-сказка / Сергей Михалков - Михалков Сергей Владимирович (Репро, 2022)
Экземпляры: БС (20220721) / Инвентарный номер: РТШ55216 / Цена: / Сис.шифр: 84(2) / Авт.знак: М 69 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-4